2021
DOI: 10.3390/cancers13143523
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Multiple Myeloma Stem Cell-Like Cells

Abstract: Multiple myeloma (MM) is a B-cell tumor of the blood system with high incidence and poor prognosis. With a further understanding of the pathogenesis of MM and the bone marrow microenvironment, a variety of adjuvant cell therapies and new drugs have been developed. However, the drug resistance and high relapse rate of MM have not been fundamentally resolved. Studies have shown that, in patients with MM, there is a type of poorly differentiated progenitor cell (MM stem cell-like cells, MMSCs). Although there is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 119 publications
0
6
0
Order By: Relevance
“…In cancer cells, this kind of durable proliferation arrest or reversible “death” promotes post-therapy tumor repopulation, and is one of the main mechanisms that contribute to drug resistance [ 109 ]. In MM, misbehaving cells in active sleep refer to the multiple myeloma stem cell-like cells, which are believed to be the major cause of minimal residual disease [ 110 ]. MM cells of immature stem-like phenotypes tend to be more quiescent, which is linked to clinical drug resistance [ 111 ].…”
Section: MM Cell Survival and Ersrmentioning
confidence: 99%
“…In cancer cells, this kind of durable proliferation arrest or reversible “death” promotes post-therapy tumor repopulation, and is one of the main mechanisms that contribute to drug resistance [ 109 ]. In MM, misbehaving cells in active sleep refer to the multiple myeloma stem cell-like cells, which are believed to be the major cause of minimal residual disease [ 110 ]. MM cells of immature stem-like phenotypes tend to be more quiescent, which is linked to clinical drug resistance [ 111 ].…”
Section: MM Cell Survival and Ersrmentioning
confidence: 99%
“…In addition, the presence of rare subpopulations of tumor cells with stem cell-like properties like greater clonogenicity, self-renewal, and differentiation capacities, are believed to significantly contribute towards treatment-refractory phenotypes in various cancers, including myeloma ( 15 ). Since our previous study had shown that CLF erodes quiescent stem-cell populations (CD34+CD38-, CFSE-bright) in drug-resistant CML patients ( 10 ), we also showed that CLF kills quiescent/dormant cells, ALDH+ cells, and side populations (SPs), collectively referred to as putative stem-like cells in myeloma, with treatment-refractory phenotypes ( 16 19 ). We propose clinical efficacy studies in relapsed/refractory myeloma using clofazimine-based drug combination regimens.…”
Section: Introductionmentioning
confidence: 91%
“…Cancer stem cells (CSC) are well-known for their quiescence, self-renewal, and drug-resistant capacity, contributing to tumor aggressiveness, treatment resistance, and tumor recurrence ( 181 ). However, the exact nature of this MM stem cell population, including the surface markers, is still largely debatable ( 182 ). Increasing evidence is indicating that dysregulation of the epigenetic machinery, including aberrant expression and/or mutations in DNA methylation modifiers, is playing a role in CSC maintenance in both solid and hematological cancers ( 183 ).…”
Section: Involvement Of Dna Methylation Modifiers In Normal Plasma Ce...mentioning
confidence: 99%